Tinea faciei, psoriasis or atopic dermatitis? - Chieco, P.; Milano, A. (European Journal of Pediatric Dermatology, 2014)
We saw an 11-year-old little girl with figured lesions of the face (Fig. 1), a little or no symptomatic, started at 6 months, which transiently responded to topical corticosteroids. The family history was full of autoimmune diseases, in particular psoriasis, and atopic manifestations, but the shape of the lesions led us to suspect tinea faciei. The mycological examination put in evidence Epidermophyton floccosum (Fig. 2a and 2b) and led us to prescribe an antifungal treatment. However, after 20 days of antifungal therapy the dermatitis worsened and was reminiscent of psoriasis (Fig. 3), for which we prescribed topical corticosteroids. The lesions responded to the treatment but recurred after its discontinuation. Ten days later at the control examination there were exudative and crusted lesions favoring the suspect of atopic dermatitis. We excluded definitively tinea faciei, diagnosed constitutional dermatitis, waiting for a future definitive diagnosis.